Derivation of Myogenic Progenitors Directly From Human Pluripotent Stem Cells Using a Sphere‐Based Culture. (21st March 2014) - Hosoyama, Tohru; McGivern, Jered V.; Van Dyke, Jonathan M.; Ebert, Allison D.; Suzuki, Masatoshi
Abstract : The authors present a novel protocol for deriving myogenic progenitors from human embryonic stem cells and induced pluripotent stem cells using free‐floating spherical culture. Results show that sphere‐based cultures of human pluripotent stem cells, expanded in medium containing high concentrations of fibroblast growth factor and epidermal growth factor, can propagate myogenic progenitors from human embryonic stem cells and healthy and disease‐specific induced pluripotent stem cells. Abstract : Using stem cells to replace degenerating muscle cells and restore lost skeletal muscle function is an attractive therapeutic strategy for treating neuromuscular diseases. Myogenic progenitors are a valuable cell type for cell‐based therapy and also provide a platform for studying normal muscle development and disease mechanisms in vitro. Human pluripotent stem cells represent a valuable source of tissue for generating myogenic progenitors. Here, we present a novel protocol for deriving myogenic progenitors from human embryonic stem (hES) and induced pluripotent stem (iPS) cells using free‐floating spherical culture (EZ spheres) in a defined culture medium. hES cell colonies and human iPS cell colonies were expanded in medium supplemented with high concentrations (100 ng/ml) of fibroblast growth factor‐2 (FGF‐2) and epidermal growth factor in which they formed EZ spheres and were passaged using a mechanical chopping method. We found myogenic progenitors in the spheres after 6 weeks of culture and multinucleated myotubes following sphere dissociation and 2 weeks of terminal differentiation. A high concentration of FGF‐2 plays a critical role for myogenic differentiation and is necessary for generating myogenic progenitors from pluripotent cells cultured as EZ spheres. Importantly, EZ sphere culture produced myogenic progenitors from human iPS cells generated from both healthy donors and patients with neuromuscular disorders (including Becker's muscular dystrophy, spinal muscular atrophy, and familial amyotrophic lateral sclerosis). Taken together, this study demonstrates a simple method for generating myogenic cells from pluripotent sources under defined conditions for potential use in disease modeling or cell‐based therapies targeting skeletal muscle.